ANALISIS EFEKTIFITAS DAN KONTRIBUSI PAJAK HOTEL DAN RESTORAN TERHADAP PAD DI KOTA PONTIANAK - B01108005, ZulFAHMI (Jurnal Pembangunan dan Pemerataan, 2016)
The study entitled "The Effectiveness and Contributions Analized of Hotel and Restaurant Taxs of Regional Revenue (PAD) in Pontianak City," This aims to analyze and known the effectiveness and contribution of tax revenue of the hotel and restaurant tax to original regional income (PAD) in Pontianak city, This is descriptive study with analysis method effectiveness and contribution.The results of study showed that 1) The effectiveness of tax revenues of hotel and restaurant tax in Pontianak so good by average as 104.15% and both the hotel and restaurant growth is fluctuated during 2008-2012. An average growth of 10,65% per year, while the effectiveness of the restaurant tax is higher on average by 111.91% growth per year with an average as 33.71%. 2) The contributions of hotel and restaurant tax to PAD is enough (high) in Pontianak, but during the period 2008-2012 to fluctuated/up and down. The average of contribution of hotel tax to the Local Taxes amounted to 10.65%. The highest contribution is a hotel tax in 2010 amounted to 13.02%, and the lowest in 2012 as 7.54%, while the contribution to the PAD average of 7.23% per year. 3) Contributions restaurant tax is higher than the hotel tax reached an average of 20.63% of the local taxes, and contribute to PAD as 14.01%. The highest contribution occurred in 2010, which in 2010 is also the highest growth in the restaurant tax. The year 2010 is also the best year in the hotel tax, where the tax contribution of the hotel in 2010, the highest in five years of observation. 4) Among the other local taxes, three types of local taxes are the highest contribution to the Tax on Acquisition of Land and Building (BPHTB), street lighting tax and restaurant tax.Keywords: hotel tax, restaurant tax, Local Taxes, PAD.